Prognostic Factors for Postoperative Visual Acuity in Patients with Rhinogenic Optic Neuropathy - Mitsuya Otsuka; Tatsuya Yunoki; Hironori Ozaki; Hirohiko Tachino; Hiromasa Takakura; Hideo Shojaku; Atsushi Hayashi (Journal of Ophthalmology)
Purpose. To examine the prognostic factors related to postoperative visual acuity in patients with rhinogenic optic neuropathy. Study Design. Retrospective observational study. Materials and Methods. We retrospectively studied the medical records for 15 eyes of 15 patients who underwent surgery for the treatment of rhinogenic optic neuropathy between 31 January 2010 and 30 April 2018 at Toyama University Hospital. The patient age, sex, preoperative and postoperative visual acuity, duration from visual deficit to surgery, use of steroids, type of rhinogenic optic neuropathy, and the part of sinus lesion were analyzed. We also examined postoperative visual acuity for patients whose preoperative visual acuity was less than light perception. Results. The type of optic neuropathy was sinusitis in 7 cases, mucocele in 5 cases, and pyocele in 3 cases. Visual acuity was improved in 9 cases and deteriorated or unchanged in 6 cases. Patients in the improvement group were significantly younger than those in the nonimprovement group (p=0.01). In univariate regression analysis, preoperative visual acuity and type of optic neuropathy significantly related to postoperative visual acuity. Finally, 4 of the 15 cases (27%) had preoperative visual acuity less than light perception, but there was an improvement in postoperative visual acuity in 2 of 4 cases (50%). Conclusions. Preoperative visual acuity is the predictive factor for postoperative visual acuity in patients with rhinogenic optic neuropathy, but even if the preoperative visual acuity is less than light perception, it can be improved by surgical treatment.